Process Parameters Optimization in Membrane Fabrication for Produced Water Treatment Using Response Surface Methodology (RSM) and Central Composite Design (CCD) - Tutuk Djoko Kusworo; Dani Puji Utomo; Annizah Rahmatya Gerhana; Hanifah Angga Putra (Dept. of Chemical Engineering, Diponegoro University, 2018)
Produced water is wastewater from oil production that must be treated well. Membrane is one alternative to water treatment technology based on filtration method. But, in the use of a membrane, there’s no exact variable optimal that influences performance of the membrane. This underlying research to assess factors that influences the performance of membrane to be more optimal. Therefore, the objectives of this study determine the optimum variable through Respond Surface Methodology and Central Composite Design. After getting the optimal condition then will check the stability of the membrane. This experiment of optimization of produced water with asymmetric membrane's Polyether sulfone (PES) using Response Surface is done with varying the Zeolite concentration by low level 1% weight and 3% weight, length of UV irradiation time low level 2 minutes and high level 6 minutes, thermal annealing low level 160 ºC and high-level 180ºC. An analyzer done in this research was by processing data research to make table and charts of the relationship between the result of this experiment with changed variable, namely variation of PES concentration, time of UV ray and thermal annealing by using Response Surface Methodology (RSM) and Central Composite Design (CCD).